Sistem Pendukung Keputusan Pemilihan Jenis Bibit Unggul Kelapa Sawit Menggunakan Metode Analytic Network Process - Amelia Rizqi Utami; S Solikhun; I Irawan (LPPM STIKOM Tunas Bangsa, 2020)
With the Decision Support System can improve the quality of research to be made. For example, in the selection of superior quality oil palm seeds for the new land planting process. However, in the selection of oil palm seedlings not only in financial terms, but must be seen from a variety of criteria such as weather which is very influential in the process of selecting superior seeds of oil palm and others. If the oil palm seedlings to be selected have met the criteria, the oil palm seedlings will be a good supporting factor. The support system applied in this study is called the Analytic Network Process (ANP). The ANP method is a procedure which is used to make decisions with many interrelated criteria. by using the ANP method, it will produce priority value weighting on all elements contained in the decision making system.